(untitled) (Theatrum historiae, 2006)
Beilis Affair (1911-1913) was the biggest anti-Semitic affair in Russia before World War I. The background of the affair was primarily political. Russian radical right wanted to use it in their campaign against political liberalism. The old primitive ritual murder accusation, a traditional element of Christian anti-Semitism, became a pretext for this affair. The so-called „blood accusation“ became more common in Russia in second half of 19th century, and the state power was ambivalent towards it. In this case, the situation was similar. Although the relations between the tsarist government and the Jews in Russia was very tense and full of suspicion and in fact, the government policy remained very repressive, government was reluctant to support this sort of accusation. The fabricated judicial trial against the Jew Mendel Beilis was actually imposed on the government by the radical right in Kiev and in the State Duma. The government was pressed by radical political parties such as the Union of Russian People, which had emerged during the first Russian revolution in 1905-1906 and was originally sponsored by the governmenal circles. Apparently, the government feared the power of popular anti-Semitic movement and pogroms which could result in political disturbances. Therefore it risked the trial against Beilis, which ended in October 1913 with a liberation verdict, in spite of manipulation and forgery of evidence. The affair demonstrated how unbalanced the tsarist Jewish-policy was and proved the authorities unprepared for the methods of modern political struggle. Another important feature of this affair was the fragmentation of the political right. Some of its members did not agree with the „blood accusation“ and believed that such „medieval superstition“ only discredited the modern anti-Semitic movement. The reaction of liberal and socialist political parties was also very important. They used the affair for defending their own position in Russian politics against the radical right and the tsarist regime.